Adolescent Experiences and their Views on Social Values Related to the Phenomenon of Verbal Sexual Harassment “Catcalling”: A Qualitative Study - Etrawati, Fenny; NurSyifa, Nada; Yuliantari, Devy (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Verbal sexual harassment, “catcalling,” has been experienced by many adolescents. In 2018, the National Study on Sexual Harassment and Assault released that 38% of men and 77% of women aged 18 years and above had experienced verbal sexual harassment. Victims' experiences are often ignored because society perceives them as catcalling, not abuse. Objectives: This study aims to identify the experiences and views of adolescents regarding social values related to verbal sexual harassment otherwise known as “catcalling”. Methods: Researchers used a qualitative approach with a phenomenological design which was conducted in March 2022. The sample was selected using a purposive sampling technique involving 26 informants aged 12-23. The key informants comprised eight victims, two perpetrators, and sixteen non-victims. Meanwhile, expert key informants were the Head of WCC Palembang Companion, the Head of the Women's Protection Division at the Palembang PPPAPM Office and the Head of the Division for Prevention of Bullying and Sexual Violence on Campus. Results: The results indicate that most informants know about catcalling. However, it is often underestimated because it has become common, and there are no sanctions for the perpetrators. Generally, catcalling occurs in crowded places such as roadsides and men's hangouts. Catcalling is usually done by strangers, especially to women for fun, and society tends to negatively stigmatize victims. Conclusions: It is hoped that those around the victim can provide positive support. In addition, the government and educational institutions need to increase education and establish clear regulations to prevent sexual harassment, including catcalling.